ANALISIS PENERIMAAN MASYARAKAT TERHADAP CRYPTO ASSET SEBAGAI INSTRUMEN HEDGING INVESTASI PERBANKAN SYARIAH - Ahmad Nurafendi; Hasnah Aziz; Muslimin; Bachtiar Kemal Harahap; Akhmad Faishal (CV. Lafadz Jaya, 2026)
The development of crypto assets in Indonesia has reached a significant stage with transaction value reaching IDR 482.23 trillion in 2025 and consumer numbers surpassing 20.19 million. On the other hand, Islamic banking in Indonesia faces challenges in diversifying sharia-compliant investment portfolios. This study aims to analyze public acceptance of crypto assets as hedging instruments in Islamic banking investment portfolios, identify legal and sharia challenges, and formulate an ideal regulatory framework. The method used is normative legal research with statutory, conceptual, and comparative approaches. The results indicate that public acceptance of crypto assets tends to be positive, especially among young age groups, but is confronted with legal uncertainty regarding the sharia status of crypto assets, extreme volatility approaching gharar and maysir elements, and the absence of a definitive fatwa from the National Sharia Council-Indonesian Ulema Council. This study recommends the establishment of a specific fatwa on crypto assets for Islamic banking, strengthening of sharia financial literacy, and harmonization of regulations between OJK, BI, and DSN-MUI to create a sharia-compliant crypto asset investment ecosystem.